Comparative Antibiotic-Resistance Patterns in Environmental vs. Clinical Isolates of Pseudomonas aeruginosa in Tertiary Hospitals - KANHOON, MALIK EJAZ AHMED; MEHMOOD, AQSA; AHMAD, IBRAR (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Pseudomonas aeruginosa is a prominent hospital-acquired infection and is famously known due to its ability to survive damp hospital settings and develop multidrug resistance. Sinks, drainage outlets and medical equipment can also be considered as environmental reservoirs capable of favoring the persistence and spread of resistant strains. The comparison of the resistance profiles among environmental and clinical isolates is essential in terms of the possibility of identifying possible links in the transmission and informing the infection-control measures in the tertiary-care hospitals. Objectives: The aim of the study was to compare the antibiotic resistance profile of environmental and clinical isolates of P. aeruginosa, establish the prevalence of multidrug resistant (MDR) and extended spectrum 10 -lactamase (ESBL) producing strains, and evaluate the possible role of hospital environments in antimicrobial resistance. Methods: The study was carried out as a cross-sectional study involving tertiary-care hospitals in Punjab, Pakistan between June 2024 and April 2025. One hundred and 0 isolates were analyzed, including 50 clinical and 50 environmental isolates. The identification was done based on the usual culture features and biochemical tests, which were facilitated by automated systems. The antimicrobial susceptibility testing was performed in the format of Kirby-Bauer disk diffusion based on CLSI 2024. The detection of ESBL was done based on the double-disk synergy test and the MDR classification was done on the basis of internationally accepted definitions. Results: Clinical isolates were more resistant to carbapenems, cephalosporins, amino-glycosides and fluoroquinolones in comparison with environmental isolates. The resistance levels of carbapenem (imipenem 52; meropenem 48) and ciprofloxacin resistance (62) were high in clinical samples compared with environmental isolates (28, 26 and 38, respectively). The prevalence of MDR was 58 percent in clinical isolates and 32 percent in environmental isolates the production of ESBL was also found in 30 percent of clinical and 14 percent of environmental isolates. Conclusion: A much higher degree of antibiotic resistance was observed in clinical isolates but the existence of MDR and ESBL-positive environmental isolates demonstrates the significance of environmental reservoirs in maintaining resistant P. aeruginosa in hospitals which requires more aggressive infection-control and stewardship initiatives.